Induction of Myxospore Formation in Stigmatella aurantiaca (Myxobacterales) by Monovalent Cations - Reichenbach, Hans (1970)
Suspension cultures of Stigmatella aurantiaca can be induced to form myxospores by addition of the monovalent cations Li(+), Na(+), NH(4)(+), K(+), or Rb(+).